Analisis Pengaruh Penggunaan Lahan Terhadap Suhu Permukaan DAN Keterkaitan dengan Fenomena Urban Heat Island Menggunakan citra Satelit Landsat (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2020)
Bandar Lampung is one of the cities that has experienced rapid development in construction and infrastructure sectors, it causes Bandar Lampung as one of the destinations for urbanization. Increased urbanization causes changes in land cover by increasing the built-up land (settlement) and decreasing vegetation land causing the increase in surface temperature which can trigger an urban heat island phenomenon. This study aims to analyze the relationship of land cover and vegetation density to surface temperature to determine the phenomenon of urban heat island in Bandar Lampung City spatially. The urban heat island phenomenon can be seen by approach analysis using remote sensing data through several extractions, namely land cover classification with supervised method, vegetation index density (NDVI) and surface temperature (LST) using the split window algorithm technique. The remote sensing data used are Landsat Satellite Imagery in 2011, 2015 and 2019. The result of processing is the distribution of surface temperature of Bandar Lampung City has increased, in 2011 the average temperature reached 23.12 ° C and rose to 33.03 ° C in 2019. The effect of land use on surface temperature has a determination coefficient of 48% and a correlation of 0,693 .